Polar bears (Ursus maritimus) in the Barents Sea area : population biology and linkages to sea ice change, human disturbance and pollution - Andersen, Magnus (University of Tromsø, 2013)
All but paper 5 of this thesis are not available in Munin: 1. Aars J, Marques T A, Buckland ST, Andersen M, Belikov S, Boltunov A & Wiig Ø.: 'Estimating the Barents Sea polar bear subpopulation size', Marine Mammal Science (2009), vol. 25(1):35-52. Available at http://dx.doi.org/10.1111/j.1748-7692.2008.00228.x 2. Andersen M, Derocher AE, Wiig Ø & Aars J.: 'Movements of two Svalbard polar bears recorded using geographical positioning system satellite transmitters', Polar Biology (2008), vol. 31:501-507. Available at http://dx.doi.org/10.1007/s00300-008-0428-x 3. Freitas C, Kovacs KM, Andersen M, Aars J, Sandven S, Mauritzen M, Pavlova O & Lydersen C.: 'Importance of fast ice and glacier fronts for female polar bears and their cubs during spring in Svalbard, Norway', Marine Ecology Progress Series (2012), 447:289-304. Available at http://dx.doi.org/10.3354/meps09516 4. Andersen M, Derocher AE, Wiig Ø & Aars J.: 'Polar bear (Ursus maritimus) maternity den distribution in Svalbard, Norway', Polar Biology (2012), vol.35:499-508. Available at http://dx.doi.org/10.1007/s00300-011-1094-y 6. Andersen M and Aars J.: 'Short-term behavioural responses of polar bears to disturbance by snowmobiles', Polar Biology (2008), vol.31:501-507. Available at http://dx.doi.org/10.1007/s00300-007-0376-x 7. Derocher AE, Wiig Ø & Andersen M.: 'Diet composition of polar bears in Svalbard and the western Barents Sea', Polar Biology (2002), vol.25:448-452. Available at http://dx.doi.org/10.1007/s00300-002-0364-0 8. Andersen M, Lie E, Derocher AE, Belikov SE, Bernhoft A, Boltunov AN, Garner GW, Skaare JU & Wiig Ø.: 'Geographic variation of PCB congeners in polar bears (Ursus maritimus), from Svalbard to the Chukchi Sea', Polar Biology (2001), vol. 24:231-238. Available at http://dx.doi.org/10.1007/s003000000201 9. Andersen M, Gwynn JP, Dowdall M, Lydersen C & Kovacs KM.: 'Radiocaesium in marine mammals from Svalbard, the Barents Sea and the North Greenland Sea', Science of the Total Environment (2006), vol. ...